Tổng quan về điều khiển mờ - Dũng, Lê Bá; Hương, Nguyễn Việt (Journal of Computer Science and Cybernetics, 2016)
The basic fuzzy set theory, fuzzy processes and fuzzy model are described in this paper. Following this, the brief of the fuzzy logic control system with different approaches is presented. Finally we discuss the future development of the fuzzy system.